Fluorescent Reporter Signals, EGFP, and DsRed, Encoded in HIV-1 Facilitate the Detection of Productively Infected Cells and Cell-Associated Viral Replication Levels - Terahara, Kazutaka; Yamamoto, Takuya; Mitsuki, Yu-ya; Shibusawa, Kentaro; Ishige, Masayuki; Mizukoshi, Fuminori; Kobayashi, Kazuo; Tsunetsugu-Yokota, Yasuko (Frontiers in Microbiology, 2012)
Flow cytometric analysis is a reliable and convenient method for investigating molecules at the single cell level. Previously, recombinant human immunodeficiency virus type 1 (HIV-1) strains were constructed that express a fluorescent reporter, either enhanced green fluorescent protein or DsRed, which allow the monitoring of HIV-1-infected cells by flow cytometry. The present study further investigated the potential of these recombinant viruses in terms of whether the HIV-1 fluorescent reporters would be helpful in evaluating viral replication based on fluorescence intensity. When primary CD4+ T cells were infected with recombinant viruses, the fluorescent reporter intensity measured by flow cytometry was associated with the level of CD4 downmodulation and Gag p24 expression in infected cells. Interestingly, some HIV-1-infected cells, in which CD4 was only moderately downmodulated, were reporter-positive but Gag p24-negative. Furthermore, when the activation status of primary CD4+ T cells was modulated by T cell receptor-mediated stimulation, we confirmed the preferential viral production upon strong stimulation and showed that the intensity of the fluorescent reporter within a proportion of HIV-1-infected cells was correlated with the viral replication level. These findings indicate that a fluorescent reporter encoded within HIV-1 is useful for the sensitive detection of productively-infected cells at different stages of infection and for evaluating cell-associated viral replication at the single cell level.